2017
DOI: 10.5505/yeditepe.2017.46220
|View full text |Cite
|
Sign up to set email alerts
|

Using different anaesthesia techniques during arthrocentesis: case series

Abstract: SUMMARYInternal derangement of the temporomandibular joint (TMJ) can be defined as a disorder of the intracapsular components of the joint, which is originated by displacement of the disc from its normal functional relationship with the condyle of the mandible and the temporal bones articular fossa. The most common symptoms of temporomandibular joint internal derangement vary from simple joint sounds to locking and pain. The aim of this case series is to evaluate the effects of GowGates anaesthesia technique, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In another study, it was suggested to apply arthrocentesis with local anesthesia due to complications of general anesthesia [ 29 ]. Emes et al [ 30 ] reported in their case series consisting of 24 patients that there is no need to use Gow-Gates anesthesia for the auriculotemporal nerve block in arthrocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was suggested to apply arthrocentesis with local anesthesia due to complications of general anesthesia [ 29 ]. Emes et al [ 30 ] reported in their case series consisting of 24 patients that there is no need to use Gow-Gates anesthesia for the auriculotemporal nerve block in arthrocentesis.…”
Section: Discussionmentioning
confidence: 99%